Illusion of control affects ERP amplitude reductions for auditory outcomes of self‐generated actions. (18th February 2021) - Seidel, Alexander; Ghio, Marta; Studer, Bettina; Bellebaum, Christian
Abstract: The reduction of neural responses to self‐generated stimuli compared to external stimuli is thought to result from the matching of motor‐based sensory predictions and sensory reafferences and to serve the identification of changes in the environment as caused by oneself. The amplitude of the auditory event‐related potential (ERP) component N1 seems to closely reflect this matching process, while the later positive component (P2/ P3a) has been associated with judgments of agency, which are also sensitive to contextual top‐down information. In this study, we examined the effect of perceived control over sound production on the processing of self‐generated and external stimuli, as reflected in these components. We used a new version of a classic two‐button choice task to induce different degrees of the illusion of control (IoC) and recorded ERPs for the processing of self‐generated and external sounds in a subsequent task. N1 amplitudes were reduced for self‐generated compared to external sounds, but not significantly affected by IoC. P2/3a amplitudes were affected by IoC: We found reduced P2/3a amplitudes after a high compared to a low IoC induction training, but only for self‐generated, not for external sounds. These findings suggest that prior contextual belief information induced by an IoC affects later processing as reflected in the P2/P3a, possibly for the formation of agency judgments, while early processing reflecting motor‐based predictions is not affected. Abstract : Previous evidence suggests that agency manipulation affects the processing of self‐ versus externally generated sounds during the P2 but not the N1 time window. We complement such evidence by showing that the magnitude of an illusion of control induced prior to sound generation affects P2, but not N1, amplitudes for the processing of self‐generated sounds. Our results demonstrate that auditory processing in the P2 time window integrates contextual belief information related to self‐performed actions.